A revision of Medon. XI. Five new species, additional records, and the first confirmed records from the Oriental region (Coleoptera: Staphylinidae: Paederinae) - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2018)
Five species of the paederine genus Medon Stephens, 1833 from the East Palaearctic and Oriental regions are described and illustrated: Medon arunicus spec. nov. (East Nepal: Arun valley) and M. acutapicalis spec. nov. (East Nepal: Theratum district) of the M. apicalis group; M. sundaicus spec. nov. (Indonesia: Java, Sulawesi) and M. sabahicus spec. nov. (Malaysia: Sabah) of the M. ferrugineus group; M. emeianus spec. nov. (China: Emei Shan) of the M. profundus group. Medon sundaicus and M. sabahicus represent the first confirmed records of the genus from the Oriental region. Additional records of 32 species and subspecies are reported, among them several new country records. Medon is now represented in the Palaearctic region by five species groups and 86 confirmed species, 23 of which are distributed in the East Palaearctic region. Nomenclatural Acts Medon arunicus spec. nov. – urn:lsid:zoobank.org:act:69F2F945-73D2-455D-A9E4-AED64A103AE8 Medon acutapicalis spec. nov. – urn:lsid:zoobank.org:act:78914E12-DB20-4D30-AA87-E81646700BC5 Medon sundaicus spec. nov. – urn:lsid:zoobank.org:act:5009E115-85F9-441E-9348-2FFCEEC75102 Medon sahahicus spec. nov. – urn:lsid:zoobank.org:act:24AF6CD2-27BC-45D4-A2AB-735AA815D552 Medon emeianus spec. nov. – urn:lsid:zoobank.org:act:30FF85B2-BAA4-466A-8544-39A67BC45938